Hematology and serum biochemistry reference intervals for the common opossum Didelphis marsupialis (2025)
ABSTRACT: The common opossum, Didelphis marsupialis, is a neotropical and synanthropic marsupial common and widespread in Latin America. The strong human-opossum conflict that results in high numbers of individuals with health problems demands information on physiological parameters to be used in veterinary medicine practice. The aim of this study was to estimate the reference intervals (RI) of hematology and serum biochemistry for this species which are lacking and evaluate its variability. Out of the 61 apparently healthy wild opossums evaluated, we found significant variability in the RI´s associated sex, life stage, habitat, and the reproductive stage of females. Males had higher values of RBC and hemoglobin than females, but females had higher values of MCH than males. Juveniles had higher values of MCV and MCH, but adults had higher values RBC, WBC and neutrophils. In addition, rural opossums had higher values of hemoglobin, MCHC, MCH and platelets, but urban opossums had higher values of WBC, particularly neutrophils and lymphocytes. Opossums are exposed to many different stressors in urban settings, and further research is needed to understand these physiological responses to urbanization. Finally, lactating females had higher values of monocytes and basophils compared to non-lactating females, potentially providing passive immunity through the milk to the immature neonates in the marsupium.